DSP-Based Sensorless Speed Control of a Permanent Magnet Synchronous Motor using Sliding Mode Current Observer - Rachid Askour; Badr Bououlid Idrissi (Institute of Advanced Engineering and Science, 2014)
In this paper, experimental results of 3-phase permanent magnet synchronous motor (PMSM) sensorless speed control are presented. To estimate the rotor position, a sliding mode current observer (SMCO) was implemented. This observer estimates the back emfs of the motor in the stationary reference frame using only the measured voltages and currents of the motor. These emfs were utilized to obtain the rotor position. The speed of the motor was calculated by differentiating the rotor position angle. The stability of the proposed SMCO was verified using Lyapunov method to determine the observer gain. The saturation function was adopted in order to reduce the chattering phenomenon caused by the SMCO. A vector control method was employed to achieve the sensorless drive system. The control application was developed in C/C++ language and implemented using the Texas Instruments TMS320LF2812 digital signal processor (DSP). This new processor enables intelligent control for motors. We used to test the drive the MCK2812 which is a professional development kit available from Technosoft Company. The theoretical finding is validated with experimental results that show the effectiveness of the real-time implementation.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5704